A Unique Case of Fungal Endometritis Caused by Aspergillus quadrilineatus in an Immunocompetent Woman and Literature Review - Fatemeh Zahra Ranjbar Golafshani; Erfan Ghaffari Lashkenari; Firoozeh Kermani; Soheila Abbaszadeh Godarzi; Saeid Mahdavi Omran (Clinical Case Reports)
ABSTRACT Abnormal uterine bleeding (AUB) is a common gynecological concern often attributed to hormonal disorders, malignancies, or infections. While bacterial and viral infections are frequently investigated, fungal infections, such as aspergillosis, are often overlooked. This case report highlights a rare instance of endometrial aspergillosis caused by Aspergillus quadrilineatus in an immunocompetent woman. A 64‐year‐old woman presented with persistent vaginal bleeding. Histopathological examination of endometrial tissue revealed septate hyphae consistent with fungal infection. Molecular analysis identified the causative agent as A. quadrilineatus. The A. quadrilineatus isolate demonstrated susceptibility to various antifungal agents, including azoles and amphotericin B. This report emphasizes the need for increased awareness of fungal infections, including aspergillosis, as a potential cause of AUB. Further research is needed to enhance understanding of the epidemiology, risk factors, and clinical manifestations of endometrial aspergillosis.